Buried but preserved: The Proterozoic Arubiddy Ophiolite, Madura Province, Western Australia - Spaggiari, C.; Smithies, R.; Kirkland, Chris; Wingate, M.; England, R.; Lu, Y. (Elsevier BV, 2018)
We describe a previously unidentified Proterozoic ophiolite complex situated in the Madura Province in southeastern Western Australia. The Madura Province is almost entirely covered by Mesozoic to Cenozoic basin rocks but new basement drillcores have revealed oceanic crustal assemblages that record continental marginal basin formation followed by oceanic subduction and basin closure. The Pinto Basalt has E-MORB/OIB chemical affinity and ?Nd(1600 Ma)from 2.54 to +3.3. It formed by mantle upwelling beneath extending crust in an ocean-continent transition zone and must be considerably older than c. 1389 Ma adakite that intrudes it. The Sleeper Camp Formation comprises mafic metavolcaniclastic schist intruded by metadolerite and plagiogranite veins. Zircon crystals from the metavolcaniclastic schist yield a dominant age component and maximum depositional age of 1536 ± 13 Ma. The metadolerite and plagiogranite veins have zircon crystallization ages of 1479 ± 8 Ma and 1471 ± 5 Ma, respectively. Interlayered basalt and sediments of the Malcolm Metamorphics have a maximum depositional age of c. 1470 Ma and were metamorphosed at 1315 ± 11 Ma. The mafic rocks from both units are tholeiitic, with MORB-like HFSE ratios that point to a depleted mantle source similar to N-MORB, but with trace element patterns that indicate subduction enrichment. V/Ti ratio trends suggest the Sleeper Camp Formation marks oceanic subduction initiation at c. 1479 Ma. The progression to oceanic arc formation is recorded by the Malcolm Metamorphics after c. 1470 Ma, and the Haig Cave Supersuite from 1415 to 1389 Ma. The majority of these rocks occur within the hanging wall of the Rodona Shear Zone and were structurally emplaced above the continental margin of the West Australian Craton between 1389 and 1330 Ma during oceanic arc–continent collision, forming the Arubiddy Ophiolite Complex. The occurrence of oceanic crustal assemblages behind the accreted ophiolite complex frozen by the emplacement of voluminous 1192–1125 Ma Moodini Supersuite ferrogabbros and granites demonstrates that continental collision did not occur between the West Australian and South Australian Cratons. The preservation of rocks of oceanic affinity behind ophiolites could be a hallmark of other Proterozoic terranes that have escaped full continent-continent collision.